Fidelidade inconteste à igreja católica e abertura aos mundos religioso e secular: a mística cristã de Chiara Lubich. - Koury, Jussara Rocha (2022)
This thesis, presented to the Postgraduate Program in Religion Sciences of the Catholic University of Pernambuco, sheds light over the Christian mystique of Chiara Lubich, founder of the Society of Mary (Focolare Movement), which began during the Second World War, in the city of Trento, northern Italy. After outlining the object of the thesis, the problem emerged from two questions: how did Chiara Lubich's mystique go beyond the monastic walls and opened the doors to the contemporary world without neglecting its Christocentric character? Is a fully aligned mystique, obedient to the Catholic Church as an institution, to overcome its walls, flooding secular worlds, without breaking with the Church itself, even feasible? This, then, is the problem that served as a streamline for our thesis. Our general objective was thus defined: to situate the impact of Chiara Lubich's Christian mysticism under the prism of her undisputed fidelity to the Catholic Church and her openness to the religious and secular worlds. The trails were defined by the specific objectives: to draw an overview of the ideologies and the Catholic Church in the first half of the 20th century, during the Second World War; to identify flashes of mystique in the childhood and youth of Chiara Lubich; to analyze the evolution of the Christian mystique of the Catholic Church until the first half of the 20th century; to investigate the mystical experience of Chiara Lubich; and to specify the rupture of walls in the religious world and the flood in the secular world caused by the mystique of Chiara Lubich. Among the theorists we use, we highlight Eric Hobsbawn and Giacomo Medina, who gave us important contributions to the history of war and the Church, respectively; Bernard McGinn, with his framework on mysticism, in addition to the great contribution we found in Roger Bastide on the same subject; Johann Baptist Metz and his proposal for a “mystique with open eyes”, which goes towards the world, especially in search of those who suffer most, to find the face of God and dive into his mystery; the story of Chiara, supported by journalists Jim Gallagher (Scottish) and Armando Torno (Italian); and the abundant bibliography available on the aspects of her mystique, especially what she herself wrote and left as a legacy, not only for the members of the Movement, but for the Church and for humanity. As this is a qualitative research, we support our methodology in Cecilia Minayo and pursue two guidelines: the first, documentary, especially in documents from the collection made available on Chiara Lubich by the official websites of the Focolare Movement and the Vatican; and the second, bibliographic, whose review goes through the aspects and authors already mentioned, as well as others, including Chiara herself. As a result, we conclude that Chiara Lubich's mystique positively impacted both the religious and secular world in various directions. With regard to the first, the proposition of experiencing a Christianity committed to daily life, and, as one of its consequences, the construction of dialogues with various Christian denominations towards ecumenism and interreligious dialogue; regarding the second, we highlight the works in fields of the modern world: economics, politics, culture, preservation of the environment, education – especially in Education for Peace, proposals that point to the establishment of fairer and more respectful relations with differences. Therefore, a mystique that permeates human relations in their diversity.